Survey of nocturnal mammals in semi-arid landscapes (Zoological Records and Reviews, 2022)
Semi-arid landscapes of the Deccan Plateau in India harbour a diverse but poorly documented nocturnal mammal fauna, with species assemblages adapted to the extreme thermal and water stress characteristic of these environments.Nocturnal mammals -- including insectivorous bats, small rodents, hedgehogs, civets, genets, and nocturnal carnivores -constitute a substantial and functionally critical component of semi-arid mammal communities that is routinelyunderdetected by diurnal survey methods. This study presents a comprehensive survey of nocturnal mammals across 42sites in the semi-arid Deccan Plateau of Andhra Pradesh, Telangana, and Karnataka, using camera trap arrays, batacoustic detectors, Sherman live-trapping, and spotlight transect surveys over two complete annual cycles (2019-2021).A total of 84 nocturnal mammal species from 18 families were documented, comprising 28 bat species, 32 rodentspecies, 12 carnivore species, and 12 other nocturnal species. Twelve species represent new state records for thesurveyed states. Camera trap data reveal that the Indian pangolin (Manis crassicaudata) and the rusty-spotted cat(Prionailurus rubiginosus) are more widely distributed in the Deccan semi-arid landscape than prior records suggested.Habitat patch size, rocky outcrop presence, and distance from the nearest human settlement are the three strongestpredictors of nocturnal mammal species richness. Hunting pressure and habitat conversion for dryland agriculture areidentified as the primary conservation threats. Fourteen species are IUCN Threatened or Near Threatened.
Keywords: conservation; carnivores; rusty-spotted cat; Indian pangolin; small mammals; camera trapping; bat acoustics; Deccan Plateau; semi-arid; nocturnal mammals